The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.vaccine.2012.10.041
|View full text |Cite
|
Sign up to set email alerts
|

A novel synthetic bipartite carrier protein for developing glycotope-based vaccines

Abstract: Development of successful vaccines against glycotopes remains a major challenge. In the current studies, we have successfully developed a novel carrier protein for glycotopes based on the concept of antigen clustering and specific stimulation of T helper cells to mount strong antibody response to glycotopes. The bipartite carrier protein consists of a tandem repeat of a cysteine-rich peptide for docking of clustered glycotopes to effectively activate B cells and an Fc domain for antigen delivery to antigen pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Recently, we have successfully produced anti‐Tn and anti‐sTn monoclonal antibodies (mAb) with high affinity and high specificity. These two antibodies recognize their cognate antigens exclusively . In this study, we have reported the reciprocal relation of Tn and sTn in OSCC progression.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Recently, we have successfully produced anti‐Tn and anti‐sTn monoclonal antibodies (mAb) with high affinity and high specificity. These two antibodies recognize their cognate antigens exclusively . In this study, we have reported the reciprocal relation of Tn and sTn in OSCC progression.…”
Section: Discussionmentioning
confidence: 75%
“…They were then treated with 0.3% H 2 O 2 for 30 min to block endogenous peroxidase; and incubated with 5% normal goat serum in phosphate‐buffered saline (PBS) for 2 h at room temperature to block non‐specific antibody reactions. After three washes with PBS containing 0.1% Tween 20 (PBST), sections were incubated with anti‐Tn (1 in 200 dilution), anti‐sTn (1 in 200 dilution) or anti‐NF‐κB antibody (1 in 200 dilution; Cell Signalling Technology, Denver, CO, USA) for 30 min at room temperature, while negative controls were incubated with PBS under the same conditions. After rinsing in PBST, tissue sections were incubated with Envision horseradish peroxidase (Dako, Glostrup, Denmark) for 30 min at room temperature and subsequently incubated with a substrate–DAB chromogen buffer (Dako), before being counterstained with Mayer's haematoxylin, dehydrated and coverslipped with mounting medium.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedures used have been described previously [25] . In brief, levels of NF-kB and RAM-1 expression in the aorta and liver tissue were determined by immunohistochemical staining using mouse anti-NF-kB and anti-RAM-11 antibodies (Dako).…”
Section: Methodsmentioning
confidence: 99%